Simultaneous triclosan degradation and nitrate reduction by a UV/Sulfite/Phenol process based on sulfite radical mechanism: dechlorination, mineralization, and bioassessment - Hossein Faraji; Mehdi Salari; Forough Riahimanesh; Hadi Rahimzadeh; Behrouz Akbari-adergani; Asieh khalilpour; Nasim Naeeji; Fatemeh Asgharzadeh (PLoS ONE, 2026)
Industrial development has increased the introduction of pollutants such as nitrate (NO₃⁻) and triclosan (TCS) into the environment, both of which pose significant environmental and health risks. The experiments were carried out in a 150 ml glass tube (photoreactor) equipped with a UV lamp (mercury vapor lamp (16 W) with a quartz cover operated at a controlled temperature (21 ± 2 °C), with an ultraviolet (UV) lamp and 2 mg/L dissolved oxygen. In the UV/sulfite process, the weak S-S bonds of sulfite, when exposed to UV radiation, produce SO3 •- radicals. The study assessed the effects of sulfite concentration, reaction time, pH, and pollutant levels on treatment efficiency. At pH 3 and 7 with 50 mg/L concentrations of TCS and NO₃ ⁻ , TCS removal efficiencies were 23% and 100%, while NO₃ ⁻ removal was 18% and 68%, respectively. Increasing sulfite from 50 to 200 mg/L improved results, achieving 85% NO₃⁻ and 100% TCS reduction in 90 minutes. SMP outperformed UV and sulfite-only treatments, achieving 68% and 100% reductions after 180 minutes. The process also led to partial nitrate-to-nitrite conversion, which decreased over time. In the SMP process, the values of Kobs (min-1) were 0.017, 0.031 for NO3- and TCS and EEM (kWh m-3), 0.3 and 0.2, respectively.Chemical oxygen demand (COD) and total organic carbon (TOC) reduced notably, and toxicity levels dropped dramatically. Given its high efficiency, low energy consumption, and minimal environmental impact, the SMP process shows significant potential for practical scale-up in wastewater treatment applications, especially in industries dealing with persistent organic pollutants and high nitrate concentrations.